Loss of Autonoetic Awareness of Recent Autobiographical Episodes and Accelerated Long-Term Forgetting in a Patient with Previously Unrecognized Glutamic Acid Decarboxylase Antibody Related Limbic Encephalitis - Witt, Juri-Alexander; Vogt, Viola Lara; Widman, Guido; Langen, Karl-Josef; Elger, Christian Erich; Helmstaedter, Christoph (Frontiers in Neurology, 2015)
We describe a 35-year old male patient presenting with depressed mood and emotional instability who complained about severe anterograde and retrograde memory deficits characterized by accelerated long-term forgetting and loss of autonoetic consciousness regarding autobiographical memories of the last three years. Months before he had experienced two breakdowns of unknown etiology giving rise to the differential diagnosis of epileptic seizures after various practitioners and clinics had suggested different etiologies such as a psychosomatic condition, burnout, depression or dissociative amnesia. Neuropsychological assessment indicated selectively impaired figural memory performance. Extended diagnostics confirmed accelerated forgetting of previously learned and retrievable verbal material. Structural imaging showed bilateral swelling and signal alterations of temporomesial structures (left > right). Video-EEG monitoring revealed a left temporal epileptic focus and subclincal seizure, but no overt seizures. Antibody tests in serum and liquor were positive for glutamic acid decarboxylase antibodies. These findings led to the diagnosis of glutamic acid decarboxylase antibody related limbic encephalitis. Monthly steroid pulses over six months led to recovery of subjective memory and to intermediate improvement but subsequent worsening of objective memory performance. During the course of treatment the patient reported de novo paroxysmal non-responsive states. Thus, antiepileptic treatment was started and the patient finally became seizure free. At the last visit vocational reintegration was successfully in progress. In conclusion, amygdala swelling, retrograde biographic memory impairment, accelerated long-term forgetting and emotional instability may serve as indicators of limbic encephalitis, even in the absence of overt epileptic seizures. The monitoring of such patients calls for a standardized and concerted multilevel diagnostic approach with repeated assessments.